Folate levels in pregnancy and offspring food allergy and eczema - Molloy, J; Collier, F; Saffery, R; Allen, K; Koplin, J; Ponsonby, A; Tang, M; Ward, A; Martino, D; Burgner, D; Carlin, J; Ranganathan, S; et al. (Wiley, 2019)
Background: High folate status in pregnancy has been implicated in the increased prevalence of allergic disease, but there are no published data relating directly measured folate status in pregnancy to challenge‐proven food allergy among offspring. The study aim was to examine the association between red blood cell (RBC) folate status in trimester three of pregnancy and allergic disease among offspring.